2018
DOI: 10.29252/jhehp.4.4.3
|View full text |Cite
|
Sign up to set email alerts
|

The Significant Association of the dupA and cagA genes of Helicobacter pylori with Peptic Ulcer

Abstract: Journal homepage: www.zums.ac.ir/jhehp Background: Helicobacter pylori play a significant etiological role in various digestive diseases. Peptic ulcer is caused by H. pylori, which destroys the duodenum mucus and is often observed in the individuals consuming tobacco, spicy and heavy meals, alcohol, coffee, and tranquilizers. Several studies have indicated that duodenal ulcer promoting genes dupA and cagA are involved in H. pylori etiology. The present study aimed to evaluate the correlation between these gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Similarly, the subsequent analysis showed that infection by cagA-positive H. pylori isolates can increase the risk of GC [35]. Gohardani et al showed that the expression of cagA was higher in Iranian patients with peptic ulcers compared to those with non-ulcer dyspepsia [41]. However, in studies conducted in Korea and Japan, there was no signi cant association between the cagA gene and the severity of gastroduodenal diseases [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the subsequent analysis showed that infection by cagA-positive H. pylori isolates can increase the risk of GC [35]. Gohardani et al showed that the expression of cagA was higher in Iranian patients with peptic ulcers compared to those with non-ulcer dyspepsia [41]. However, in studies conducted in Korea and Japan, there was no signi cant association between the cagA gene and the severity of gastroduodenal diseases [42,43].…”
Section: Discussionmentioning
confidence: 99%